THE PREVALENCE OF HYPERTENSION, OBESITY, DIABETES AND JOB SATISFACTION AMONG PUBLIC HEALTH WORKERS IN CENTRAL PROVINCE, SRI LANKA - Senevirathne, C P; Katulanda, P; Dhanapala, N D (LIFE: International Journal of Health and Life-Sciences, 2015)
Aim of this study was to assess the prevalence of hypertension, obesity, overweight, diabetes and job satisfaction among public health workers in the Central province, Sri Lanka. This cross sectional study was conducted in three districts in the Central Province, Sri Lanka. Data were collected from public health workers (PHW) (n= 336). BMI, blood pressure and random blood sugar were measured. General information and self-reported job satisfaction and coping strategies were collected by a self-administered questionnaire. Mean age of PHW was 42.5 (SD 10.3, CI=95%). There were 302 females (89%) in the group. Prevalence of overweight and obesity among PHW were 29. 5% and 16.4% respectively. Among the group 26.4 % individuals (n=89) were hypertensive and 21 (6%) individuals were living with diabetes. 57.1% of individuals (n=192) reported with moderate pressure on their work. Extremely satisfied, very satisfied and moderately satisfied unsatisfied and not at all satisfied were 31.5%, 61%, 5.4 %, 1.2% and 0.6 respectively. Field work, work load, working environment, income were found to be as the common sources for stressful circumstances at work. Study revealed that overweight and obesity prevalence among public health workers in the Central Province is considerable. Significant amount of public health workers were hypertensive and living with diabetes. More than half from the group had a moderate satisfaction with their job.